Cancer patients with community-acquired pneumonia treated in intensive care have poorer outcomes associated with increased illness severity and septic shock at admission to intensive care: a retrospective cohort study. Issue 1 (December 2015) - José, Ricardo; Mohammed, Ali; Goldring, James; Chambers, Rachel; Brown, Jeremy; Agarwal, Banwari
Abstract Patients with community-acquired pneumonia (CAP) and an underlying diagnosis of cancer have worse outcomes. However, the characteristics of cancer patients with CAP admitted to intensive care units (ICUs) are not well established. In a retrospective observational study, patients admitted to a London university hospital ICU between January 2006 and October 2011 with a primary diagnosis of CAP were included. Demographic, clinical, laboratory, and outcome data were collected from the ICU and hospital pathology databases. The analysis included 96 patients with CAP, 19 of whom had an existing diagnosis of cancer. Patients with cancer had a longer median time interval between hospital and ICU admission (1 vs 2 days, p = 0.049). On admission to ICU, there were no differences in white cell count, C-reactive protein, clotting, renal function, liver function, heart rate, temperature, systolic blood pressure or oxygenation index between patients with or without cancer. However, patients with cancer had significantly lower haemoglobin levels (median 8.6 vs 10.0 g/dl, p = 0.010) and lowest diastolic blood pressure (median 40 vs 50 mmHg, p = 0.026), and higher sodium levels (median 142 vs 139 mmol/l), p = 0.020), APACHE II (median 25 vs 20, p = 0.009), SAPS II (median 51 vs 43, p = 0.039) and SOFA (median 12 vs 9, p = 0.018) scores. There were no statistically significant differences in the proportion of patients receiving mechanical ventilation or renal support, the duration of mechanical ventilation or ICU or hospital length of stay. Patients with cancer were more likely to receive vasopressors (89.5% vs 63.6%, p = 0.030) and had increased ICU (68.4% vs 31.2%, p = 0.004) and hospital (78.9% vs 33.8%, p = 0.001) mortality. The limitations of this study are its relatively small sample size and those associated with the retrospective study design. In conclusion, cancer patients with CAP had an increased risk of death that was associated with increased illness severity and prevalence of septic shock at the time of ICU admission, suggesting there may be a delay in recognition for the need for intensive care support in these patients.